Multi-field coupling analysis of twin-roll casting process for achieving thin aluminum strip high-speed casting and fabricating laminated metal cladding materials - Ce Ji; Xin Di; Xudong Liu; Shibin Liu; Jianmin Song; Huagui Huang (Case Studies in Thermal Engineering)
The twin-roll casting (TRC) process integrates solidification with deformation while emerging as a key research direction aligned with advancements in green and sustainable development. However, low casting velocity and non-uniform solidification significantly constrain both process efficiency and material performance. To address these challenges, a multi-field coupling investigation was performed using a cellular automaton-finite element (CAFE) model to analyze transient heat transfer and steady-state solidification structures. The effect of casting velocity, nucleation rate, and casting roller materials on the heat transfer and solidification structure was analyzed, indicating that the main reason for improving casting velocity by using copper roller sleeves is to improve the nucleation rate and ensure the plastic strain simultaneously. In the twin-roll solid-liquid cast-rolling bonding (TRSLCRB) process for laminated metal cladding production, three substrate parameters, including feeding position, thickness, and material composition, were identified as critical determinants of heat transfer behavior and solidification morphology. For the multi-roll solid-liquid cast-rolling bonding (MRSLCRB) process targeting round-section cladding materials, the designed inverted conical cast-rolling area demonstrates the potential for optimizing grain refinement through synergistic interaction with ultrasonic vibration fields. The implemented CAFE-based multi-field coupling methodology provides systematic guidance for both process parameter optimization and microstructure-property control strategies.